PLC Controlled Roller Clamp Automatic Assembly Machine / S. S. Ngu ... [et al.] - S. S., Ngu; L. C., Kho; T. P., Tan (2014)
This work deals with the mechanical design of the automatic assembly system for the roller clamps. The assembly system will be working in high speed condition with high yield. A rotary assembly machine is proposed in this paper. The function of different machine parts that performed the assembly processes is explained in detail. The machine control system is designed and analyzed. Then human machine interface (HMI) is presented. Experimental operation results show that roller clamps can be assembled at high speed and high efficiency thus reducing labor power and production cost.